Combination of Filter Media with Blood Shells on Water Quality and Growth of Asian Redtail Catfish (Hemibagrus nemurus) in the Recirculation System - Karisma Agung; Rusliadi Rusliadi; Mulyadi Mulyadi (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
This study aims to determine the effect of combining blood clam shell (Anadara granosa) filter media on water quality in the recirculation system for Asian Redtail catfish (Hemibagrus nemurus) maintenance. The study was conducted from December 2025 to February 2026 at the Cultivation Technology Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau, using a Completely Randomized Design (CRD) experimental method with four treatments and three replications. The treatments consisted of P0 (control without blood clam shell), P1 (150 g/25 L of water), P2 (200 g/25 L of water), and P3 (250 g/25 L of water). The results showed that the use of blood clam shells as a filter medium was able to maintain water quality during cultivation, with a temperature range of 24–28.6°C, pH 2.16–7.94, DO 4.96–6.47 mg/L, TDS 22–1038 mg/L, ammonia 0.015–1.429 mg/L, and nitrate 0.0604–21.2729 mg/L. The best treatment was obtained at P3, with a final fish length of 16.8 cm, SGR of 3.60%, feed efficiency of 93.45%, and the lowest FCR of 1.07. The fish survival rate ranged from 87–96%.